HAND AND BODY LOTION FORMULATION OF AVOVO SKIN EXTRACT (PERSEA FREESIMA GAERTN) AS A MOISTURIZER - Rani, Yosi Darmi; Delima, Cici (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Avocados have been used by the community for generations as traditional medicinal ingredients. Avocado (Persea Americana Mill) is a plant that contains many compounds that are antioxidants. Flavonoids and tannins are compounds that have antioxidant activity which are suspected as sunscreens. Research Objectives To determine the concentration of avocado skin extract (Persea Gratissima Gaertn) 3%, 5%, 7% as hand and body lotion. Laboratory experimental research. Based on the results of the one-way ANOVA test that was used to analyze the avocado peel extract as skin flexion at blank concentrations of 3% concentration, 5% concentration and 7% way concentration, the mean Squaer result was 0.333 with results 0.052 > 0.05. it can be said that the results of the table above indicate that avocado skin can be used as skin moisture. Conclusion Based on the results of community tests conducted by the three hand and body lotion formulas, avocado skin extract that has been stored for 28 days of storage shows that the skin of the fruit can be used as moisture skin.